Pathology Trainee Redeployment and Education During the COVID-19 Pandemic: An Institutional Experience - Paloma del C. Monroig-Bosque MD, PhD; Jim W. Hsu MD, PhD; Michelle S. Lin MD; Ahmed N. Shehabeldin MD; John T. Rogers MD; Charlotte F. Kim MD; Ayaz G. Kalsekar MD; Zhicheng Jin PhD; Lukas R. Cara MD; Andreia N. Barbieri MD; Ziad El-Zaatari MD; Ghazaleh Eskandari MD; et al. (Elsevier, 2020)
Pathology training programs throughout the United States have endured unprecedented challenges dealing with the ongoing coronavirus disease 2019 pandemic. At Houston Methodist Hospital, the Department of Pathology and Genomic Medicine planned and executed a trainee-oriented, stepwise emergency response. The focus was on optimizing workflows among areas of both clinical and anatomic pathology, maintaining an excellent educational experience, and minimizing trainee exposure to coronavirus disease 2019. During the first phase of the response, trainees were divided into 2 groups: one working on-site and the other working remotely. With the progression of the pandemic, all trainees were called back on-site and further redeployed within our department to meet the significantly increased workload demands of our clinical laboratory services. Adjustments to trainee educational activities included, among others, the organization of a daily coronavirus disease 2019 virtual seminar series. This series served to facilitate communication between faculty, laboratory managers, and trainees. Moreover, it became a forum for trainees to provide updates on individual service workflows and volumes, ongoing projects and research, as well as literature reviews on coronavirus disease 2019-related topics. From our program's experience, redeploying pathology trainees within our department during the coronavirus disease 2019 pandemic resulted in optimization of patient care while ensuring trainee safety, and importantly, helped to maintain continuous high-quality education through active involvement in unique learning opportunities.